The effect of HIV counselling and testing on HIV acquisition in sub-Saharan Africa: a systematic review. (16th August 2016) - Rosenberg, Nora E; Hauser, Blake M; Ryan, Julia; Miller, William C
Abstract : Objectives: Annually, millions of people in sub-Saharan Africa (SSA) receive HIV counselling and testing (HCT), a service designed to inform persons of their HIV status and, if HIV uninfected, reduce HIV acquisition risk. However, the impact of HCT on HIV acquisition has not been systematically evaluated. We conducted a systematic review to assess this relationship in SSA. Methods: We searched for articles from SSA meeting the following criteria: an HIV-uninfected population, HCT as an exposure, longitudinal design and an HIV acquisition endpoint. Three sets of comparisons were assessed and divided into strata: sites receiving HCT versus sites not receiving HCT (Strata A), persons receiving HCT versus persons not receiving HCT (Strata B) and persons receiving couple HCT (cHCT) versus persons receiving individual HCT (Strata C). Results: We reviewed 1635 abstracts; eight met all inclusion criteria. Strata A consisted of one cluster randomised trial with a non-significant trend towards HCT being harmful: incidence rate ratio (IRR): 1.4. Strata B consisted of five observational studies with non-significant unadjusted IRRs from 0.6 to 1.3. Strata C consisted of two studies. Both displayed trends towards cHCT being more protective than individual HCT (IRRs: 0.3–0.5). All studies had at least one design limitation. Conclusions: In spite of intensive scale-up of HCT in SSA, few well-designed studies have assessed the prevention impacts of HCT. The limited body of evidence suggests that individual HCT does not have a consistent impact on HIV acquisition, and cHCT is more protective than individual HCT.